2023
DOI: 10.1186/s13046-023-02788-w
|View full text |Cite|
|
Sign up to set email alerts
|

MKRN1 promotes colorectal cancer metastasis by activating the TGF-β signalling pathway through SNIP1 protein degradation

Yi Zhang,
Qin-shan Li,
Hong-lin Liu
et al.

Abstract: Background The Makorin ring finger protein 1 (MKRN1) gene, also called RNF61, is located on the long arm of chromosome 7 and is a member of the RING finger protein family. The E3 ubiquitin ligase MKRN1 is closely linked to tumour development, but the exact mechanism needs to be elucidated. In this study, we aimed to investigate the specific mechanism and role of MKRN1 in colorectal cancer (CRC) development. Methods MKRN1 expression in CRC was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Furthermore, flow cytometry analysis revealed that MKRN1 knockdown impeded the transition of HeLa cells from the G0/G1 phase to the S phase, indicating a role for MKRN1 in regulating the cell cycle. Our findings were consistent with previous studies that have identified MKRN1 as a key regulator of cell proliferation in various cancer types, such as pancreatic cancer 15 , renal clear cell carcinoma 16 , and colorectal cancer 17 . Further research is needed to elucidate the molecular mechanisms underlying the role of MKRN1 in regulating cancer cell migration and invasion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, flow cytometry analysis revealed that MKRN1 knockdown impeded the transition of HeLa cells from the G0/G1 phase to the S phase, indicating a role for MKRN1 in regulating the cell cycle. Our findings were consistent with previous studies that have identified MKRN1 as a key regulator of cell proliferation in various cancer types, such as pancreatic cancer 15 , renal clear cell carcinoma 16 , and colorectal cancer 17 . Further research is needed to elucidate the molecular mechanisms underlying the role of MKRN1 in regulating cancer cell migration and invasion.…”
Section: Discussionsupporting
confidence: 93%
“…The gene is located on human chromosome 7, contains eight exons and seven introns, and its full cDNA length is 1449 nt. MKRN1 has been implicated in diverse biological processes, including ubiquitin-mediated protein degradation, mRNA splicing, and regulation of gene expression 11 . Emerging evidence suggests that MKRN1 may function as an oncogene or tumor suppressor, depending on the context and cancer type.…”
Section: Introductionmentioning
confidence: 99%